Review of Wire Arc Additive Manufacturing for 3D Metal Printing - Li, Johnnieew Zhong; Alkahari, Mohd Rizal; Rosli, Nor Ana Binti; Hasan, Rafidah; Sudin, Mohd Nizam; Ramli, Faiz Redza (International journal of automation technology, 2019)
Wire arc additive manufacturing (WAAM) is a crucial technique in the fabrication of 3D metallic structures. It is increasingly being used worldwide to reduce costs and time. Generally, AM technology is used to overcome the limitations of traditional subtractive manufacturing (SM) for fabricating large-scale components with lower buy-to-fly ratios. There are three heat sources commonly used in WAAM: metal inert gas welding (MIG), tungsten inert gas welding (TIG), and plasma arc welding (PAW). MIG is easier and more convenient than TIG and PAW because it uses a continuous wire spool with the welding torch. Unlike MIG, tungsten inert gas welding (TIG) and plasma arc welding (PAW) need an external wire feed machine to supply the additive materials. WAAM is gaining popularity in the fabrication of 3D metal components, but the process is hard to control due to its inherent residual stress and distortion, which are generated by the high thermal input from its heat sources. Distortion and residual stress are always a challenge for WAAM because they can affect the component’s geometric accuracy and drastically degrade the mechanical properties of the components. In this paper, wire-based and wire arc technology processes for 3D metal printing, including their advantages and limitations are reviewed. The optimization parametric study and modification of WAAM to reduce both residual stress and distortion are tabulated, summarized, and discussed.